Trends and irregular variation of spatial temperature differences in the high-latitude coastal city of Turku, Finland - Suomi Juuso; Meretoja Miika (INTER-RESEARCH, 2022)
Spatio-temporal dynamics of urban heat island (UHI) and other spatial temperature variations were studied for a 17 yr period (2002-2018) in the mid-sized (193 000 inhabitants in 2019) coastal city of Turku in south-western Finland. The study was based on GIS data and 30 min interval air temperature observations from 52 observation sites in the city and its surroundings. Correlation and regression analyses, image interpretation and various GIS methods were used to investigate temperature dynamics and associated factors on a diurnal, monthly and seasonal basis. The results showed relative cooling and warming trends of certain areas as well as fluctuating and random variation of the coldest and warmest regions, respectively. Relative cooling trends were observed in semi-urban and urban areas that remained unchanged during the study period. Relative warming trends were most common in semi-urban areas where urbanization and construction of new buildings occurred rapidly. Fluctuating variation was mainly related to variation in weather conditions, especially the severity of winter and related sea-ice extent on the archipelago south-west of the city. The UHI intensity showed a slight, albeit statistically significant, intensifying trend of 0.11 degrees C per decade. Our findings demonstrate the dynamic nature of spatio-temporal intra-urban temperature differences, a fact that should more actively be taken into account in climate-related urban planning in general.